Outcomes of Lateral Tarsal Strip in Conjunction with a Minimal Skin Muscle Excision Underlying Cauterization in Korean Patients with Involutional Entropion - Lee, Hyunkyu; Cha, Eunhyang; Baek, Sehyun (Frontiers in Surgery, 2022)
We reviewed the medical records of 53 involutional entropion patients, who underwent lateral tarsal strip(LTS) with a minimal skin muscle excision by cauterization from March 2014 to December 2017 to evaluate the effectiveness and efficiency of LTS in conjunction with a minimal skin muscle excision using cautery in patients with involutional entropion. We evaluated the success rate, complications, recurrence rate and degree of satisfaction of our technique. Of 53 patients, there were 5 bilateral cases, for a total of 58 eyelids. The average of age was 71.2 years old. The average follow-up period was 18 months. Success rate for involutional entropion correction was 98.1% with our technique. There was one mild recurrence case at 7 months. In our study, the average operation time was 20.8 minutes for 48 unilateral cases and 27.2 minutes for 5 bilateral cases without intraoperative complications. Of 42 responders of patients’ satisfaction questionnaire, the 38 patients showed good satisfaction and were willing to recommend the surgery to their acquaintances. The technique of LTS c minimal skin excision with cauterization is effective and provides satisfying outcome to patients with the involutional entropion.